2006
DOI: 10.1503/cmaj.050674
|View full text |Cite
|
Sign up to set email alerts
|

Variation in health services utilization among ethnic populations

Abstract: Research R acial and ethnic disparities in the use of health services and in health outcomes have been extensively studied and well documented in the United States and the United Kingdom. Studies from both countries reveal that black, Hispanic and Asian people are less likely to access health care and experience more barriers than people who are not visibly members of ethnic minorities -that is, white people.1-7 The factors underlying ethnic disparities in health service usage are complex and could include suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(108 citation statements)
references
References 30 publications
5
98
0
4
Order By: Relevance
“…Quan et al (24) analyzed a Canadian national survey and found that ethnic minorities were just as likely as white respondents to report seeing a family physician/general practitioner or a specialist physician, where a family physician referral is required. Hemmelgarn et al (25) compared the use of peritoneal dialysis among East Asian, South Asian and white patients with end-stage renal disease initiating dialysis therapy in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Quan et al (24) analyzed a Canadian national survey and found that ethnic minorities were just as likely as white respondents to report seeing a family physician/general practitioner or a specialist physician, where a family physician referral is required. Hemmelgarn et al (25) compared the use of peritoneal dialysis among East Asian, South Asian and white patients with end-stage renal disease initiating dialysis therapy in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies [8,20,21] have demonstrated inequities in access to health care services among immigrants compared to the host population in developed nations. These studies have shown that immigrants tend to underutilize health care services compared to the host population.…”
Section: Patterns Of Ed Care Usementioning
confidence: 99%
“…16 Despite its wide spread use in health services research, the Aday-Andersen framework 7 is merely a theoretical framework for analyzing the factors rather than providing a mathematical model with precise variables or providing precise methods to be used. The choice of factors depends on the extent of prior research, the research question, the purpose of the study, and data availability.…”
Section: Aday-andersen Framework Versus Epidemiologymentioning
confidence: 99%
“…Characteristics of both studies included use of multi-stage complex sampling procedures, a cross-sectional survey, one time random telephone survey (land line only) of none institutionalized adults (very low income populations, who may be less likely to own telephones, may be under sampled). None of the authors made mention of a framework in the introduction and design sections (Quan et al 16 cited Aday-Andersen under interpretation). This omission of framework is probably justified given the secondary nature of the data.…”
Section: Assessing Need For Health Servicesmentioning
confidence: 99%
See 1 more Smart Citation